#TITLE_ALTERNATIVE# - YUSUF SAMAD, M.
The objective of this research is to find an alternative analysis of zinc in trace amounts. This research is still in its elementary stage and need to be developed further, so that at present the aspect is mainly qualitative. In this research Rhodamine B is used in expectation that it will complex the metal analyzed and subsequently it can be measured by visible spectrophotometry. The choice fell on Rhodamine B because of its high absorption coefficient as this is essential for high sensitivity colorimetry. The data showed that Rhodamine B, Zinc and Thiocyanate can react to form (RB)2Zn(CNS)4 in acid solutions with >A maximum about the same as Rhodamine B. This means that for the analysis the complex must be extracted prior to the measurement. In contrary to the complex, Rhodamine B itself is not soluble in many organic solvents, so the purification of the complex can be easily affected by using selected solvents. For quantitative purposes, it is suggested to work at a pH = 3 (ambient temperature) using a RB concentration of 2.2 x 10 4M and a CNS concentration of 0.18 M. The coefficient variation of the analysis is 2-10% within a limit of detection 1-6.5 ug Zn/3 mL.